Hubungan Penggunaan Kontrasepsi Suntik dengan Perubahan Siklus Menstruasi pada Akseptor KB - Safira Devi Zafarina; Tri Iriyani; Tutik Ekasari (Puslitbang Sinergis Asa Professional, 2026)
Family Planning (FP) is a strategic effort in birth control and improving maternal welfare. One of the most widely used contraceptive methods is injectable contraception, both 1-monthly and 3-monthly injections. The use of injectable contraception can cause hormonal side effects, one of which is changes in the menstrual cycle. The purpose of this study was to analyze the relationship between injectable contraception use and changes in the menstrual cycle in family planning users. This study used a correlative design with a cross-sectional approach. The study population was all 95 mothers who accepted injectable contraception at PMB Ani Farmadiani, using an accidental sampling technique. Data were collected using questionnaires and observation sheets, then analyzed using the chi-square test with the help of SPSS. The results showed that most users of 3-monthly injectable contraception experienced irregular menstrual cycles, while users of 1-monthly injectable contraception tended to have regular menstrual cycles. Statistical tests showed a p-value of 0.005 (p<0.05), indicating a significant relationship between injectable contraception use and changes in the menstrual cycle. The conclusion of this study is that there is a relationship between injectable contraception use and changes in the menstrual cycle, where changes occur more frequently in users of 3-monthly injectable contraception. It is hoped that the results of this study can be used as a consideration for health workers in providing contraceptive counseling to family planning acceptors.